Topoisomerases inhibition and DNA binding mode of daunomycin-oligoarginine conjugate - Valeria Visone; Ildikó Szabó; Giuseppe Perugino; Ferenc Hudecz; Zoltán Bánóczi; Anna Valenti (Taylor & Francis Group, 2020)
Cancer is a major health issue adsorbing the attention of a biomedical research. To fight this disease, new drugs are developed, specifically tailored to target biological pathways or peculiar components of the tumour cells. Particularly interesting is the use of intercalating agents as drugs capable to bind DNA and inhibit enzymes involved in DNA metabolism. Anthracyclines are the most commonly used anticancer drugs. In particular, daunomycin is used to cancer treatment by exploiting its ability to intercalate DNA and inhibit the activity of DNA topoisomerases implicated in the replication processes. Unfortunately, clinical application of anthracyclines is limited by their side effects. The conjugation with specific carriers could affect the selectivity and reduce side effect by improving stability and/or cellular uptake properties. We here report the biochemical characterisation of a daunomycin oligopeptide conjugate containing six residues of arginine, by the analysis of its fluorescence properties, DNA interaction and topoisomerases inhibitory effects.